THE EFFECTIVENESS OF SECONDARY SCHOOL STUDENTS' MULTILINGUAL SKILLS IN THE DIGITAL ERA - Widia Tamara; Arista Ardilla; Andriani (RADJA PUBLIKA, 2022)
The development of technology has brought major changes in various aspects of life, including in education. This study aims to analyze the effectiveness of using technology in multilingual learning in primary schools, focusing on the implementation in Lhokseumawe City. A mixed methods approach was used. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were analyzed using thematic analysis methods. The results showed that the use of technology in language learning had a positive impact on improving students' speaking, listening, reading and writing skills. The group of students who used technology experienced an average score increase of 15%, compared to an 8% increase in the group who learned with traditional methods. In addition, the use of gamification-based apps and e-learning increased students' motivation and engagement in learning. However, the main challenges faced were limited access to digital devices and internet connectivity, as well as a lack of training for teachers in optimizing technology in teaching. The conclusion of this study confirms that technology integration in multilingual learning can improve learning effectiveness, provided it is supported by adequate infrastructure and improved teacher competencies. Therefore, a comprehensive strategy is needed to overcome the existing constraints, including equal access to technology in primary schools and the development of a more adaptive digital-based curriculum.